Government supervision of the implementation of diversion In the child criminal justice system: Constitutional law perspective - Dhea Aulia Azzahra; Harmono Harmono (CV. AFDIFAL MAJU BERKAH, 2026)
The paradigm shift in Indonesia's juvenile criminal justice system from a retributive approach to restorative justice through diversion mechanisms is a constitutional mandate to protect children's fundamental rights. However, in its implementation, diversion is often trapped in administrative formalities and sociological barriers, such as the dominance of compensation agreements that violate the principle of justice for economically disadvantaged groups. This study aims to analyze the regulation of authority and government oversight mechanisms for the implementation of diversion at the investigation, prosecution, and court hearing levels from a Constitutional Law perspective. The research method used is normative juridical with a statutory and conceptual approach. The results show that although Law Number 11 of 2012 (the Juvenile Justice and Juvenile Justice Law) and Government Regulation Number 8 of 2017 have provided a legal basis for hierarchical supervision by direct superiors and functional supervision by the Community Guidance (PK) of Bapas, their effectiveness remains fragmented. This study concludes that strengthening the oversight mechanism should not stop at administrative reporting, but must also address aspects of institutional accountability through synchronization of cross-sectoral regulations and optimization of digital systems such as SPPT-TI. Revitalization of the role of external supervisory institutions is needed to ensure that the discretionary authority of officers remains within the corridor of the best interests of children and the principles of the rule of law that guarantee restorative justice evenly and sustainably.